Evaluating low impact development practices potentials for increasing flood resilience and stormwater reuse through lab-controlled bioretention systems - Marina Batalini de Macedo (IWA Publishing, 2021)
Low impact development practices (LID) as alternative measures of urban drainage can be used within the approach of resources recycling and co-management. This study evaluates the potential contribution of a bioretention system to flood control, non-potable water demands (NPD) and resources co-management. Bioretention setups were tested experimentally under variable conditions to identify operational key-factors to multiple purposes. Additionally, the efficiencies obtained for laboratory scale were extrapolated for household and watershed scale, quantifying the indicators of water demand reduction (WDR), energy demand reduction (EDR) and carbon emission reduction (CER) for hybrid systems with LID. The laboratory results indicated that the use of a bioretention with a submerged zone can improve the quality of the water recovered for reuse, while maintaining the efficiency of runoff retention and peak flow attenuation. Comparing the bioretention effluent quality with the Brazilian standards for stormwater reuse, the parameters color, turbidity, E. coli and metals were above the limits, indicating the necessity of a better treatment for solids particles and disinfection. Expanding the analysis to watershed scale, the bioretention helped to reduce NPD demands up to 45%, leading to a reduction in energy demand and carbon emission from the centralized water supply system. HIGHLIGHTS Bioretention prototype is evaluated for flood resilience and non-potable water demands.; Bioretention setups are tested under variable rainfall, soil saturation and head losses.; Water reuse for non-potable demands require better pollutant removal rates.; Stormwater harvesting decreases water stress, energy demands and carbon emission.; Monetary savings through stormwater harvesting were obtained.;